Corn Grain Yield and Soil Properties after 10 Years of Broiler Litter Amendment. (1st September 2016) - Netthisinghe, A. M. P.; Woosley, P. B.; Gilfillen, R. A.; Willian, T. W.; Sistani, K. R.; Rowland, N. S.
Abstract : Use of broiler litter (BL) nutrients for crop production benefits crops, soils, and aids in disposing manure. Understanding corn ( Zea mays L.) grain production and soil properties resulting from long‐term BL amendment helps establish a sustainable manure‐based corn production with low environmental risk potential. This study conducted at Bowling Green, KY, during 2005 to 2015 examined effects of supplying N requirement of corn grain crop monoculture by broiler litter (full broiler litter, FBL), 1:1 mixture of BL and inorganic N (half broiler litter rate, HBL), and chemical fertilizer (CF) on corn grain yield and post‐harvest soil properties under no‐till (NT) and conventional tillage (CT). The FBL produced significantly higher grain yield (10.1 Mg ha −1 ) than the HBL (9.6 Mg ha −1 ), but similar to CF (9.8 Mg ha −1 ). The FBL soils had greater cation exchange capacity (CEC), organic matter (OM), and total nitrogen (TN) (15.5 cmol kg −1 ; 45 and 2.9 g kg −1 ) than the HBL (12.3 cmol kg −1 ; 42.3 and 2.4 g kg −1 ) and CF (10.1 cmol kg −1 ; 35.5 and 1.7 g kg −1 ). The FBL and HBL soils had 478 and 270 mg P kg −1 ; 15.7 and 9.6 mg Cu kg −1 ; 40.9 and 21.1 mg Zn kg −1 levels, respectively. Soil pH increased in the FBL, but decreased in CF. Soil nutrient aggregation rate was greater in the NT. Having lower soil nutrient accumulation than FBL and equivalent grain production potential as CF, HBL offers a better option for corn grain production with BL than by FBL. Core Ideas This study examined effects of long‐term broiler litter amendment on corn grain yield and post‐harvest soil properties. Broiler litter at full and half rates has similar corn grain production potential as chemical fertilizer. Broiler litter induced high soil nutrient levels, but levels elevated by half litter rate was not environmentally significant. No‐till and conventional tillage treatments have similar agronomic benefits and environmental risks.